Radar Technology for Coastal Areas and Open Sea Monitoring - Ludeno, Giovanni; Uttieri, Marco (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Monitoring oceans and coastal areas has a fundamental social impact, and this scenario is made still more challenging with the present and future issues related to climate change. In this context, radar systems have gained increasing interest, since they are remote sensing devices capable of providing information about sea waves, currents, tides, bathymetry, and wind. Moreover, radar systems can be designed to perform both large-scale and small-scale monitoring, with different spatial and temporal resolutions, and can be installed on different observation platforms (ship-based, ground-based, airborne, satellite or drones). In this regard, this book aims at engendering a virtual forum for ocean radar researchers, where state-of-the-art methodologies and applications concerning ocean monitoring by means of radar technologies are reviewed and discussed.